PENERAPAN MODEL PEMBELAJARAN NOVICK UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA DI KELAS X SMAN 5 PEKANBARU - Ritonga, Deriani; Irianti, Mitri; Azhar, Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe the learning outcomes of students who apply Novick learning models in class X linear motion material at SMAN 5 Pekanbaru and determine differences in student learning outcomes through applying Novick learning models with conventional learning in linear motion materials in class X SMAN 5 Pekanbaru . The research method used was quasy experiment with Intact Group Comparison design. The population is all students of class X MIPA SMAN 5 Pekanbaru. A sample selected by random sampling totaling 36 people as the experimental class and totaling 36 people as the control class. This research instrument was in the form of a written test of cognitive learning outcomes in the form of multiple choice. Data was collected by giving a posttest to the study sample. Data analysis in this study uses descriptive analysis and inferential analysis. The results showed in the experimental class the average absorption of students reached 75.56% with a good category and the control class 68.89% with a fairly good category. From the average absorption scores obtained, the effectiveness of learning in the experimental class is in the effective category and the control class isin the quite effective category. Based on the results of inferential analysis, there are significant differences in students' cognitive learning outcomes between classes applying Novick's learning model and classes applying conventional learning on linear motion material. Thus, Novick's learning model can improve cognitive learning outcomes of students in class X of SMAN 5 Pekanbaru on linear motion material.Key Words: Novick Learning Model, Cognitive Learning Outcomes, Linear Motion